Research Trend in Coastal Sediment Transport Using Numerical and Empirical Models - Hamid, Nor Baizura; Mokhtar, Mardiha; Daud, Mohd Effendi (Journal of Advanced Industrial Technology and Application, 2026)
Coastal sediment transport remains a critical research domain due to its implications for shoreline stability, erosion management, and sustainable coastal development. Despite extensive studies, challenges persist in integrating numerical and empirical models to capture the complex dynamics of sediment movement under varying hydrodynamic conditions. This study addresses the research gap by conducting a bibliometric analysis of global scientific literature on coastal sediment transport using numerical and empirical approaches. Data were retrieved from the Scopus database through advanced search techniques, yielding 1,089 publications. The dataset was first processed using OpenRefine to clean and harmonize author names, keywords, and affiliations, ensuring accuracy and consistency. Statistical trends, including annual publication growth, prolific authors, contributing journals, and leading countries, were examined through the Scopus analyzer. Furthermore, visualization of research networks such as co-authorship, keyword co-occurrence, and citation patterns was performed using VOSviewer, offering insights into the structural relationships within the field. Results reveal a steady increase in publications over the last two decades, with the United States, China, and the United Kingdom emerging as central contributors through high productivity and extensive collaboration networks. Frequently occurring keywords highlight a strong focus on sediment transport modeling, shoreline evolution, and climate change-driven coastal dynamics. The visualization further identifies clusters of international collaboration and thematic research streams, reflecting the interdisciplinary nature of the field. Overall, this bibliometric study provides a comprehensive overview of research trends, key contributors, and collaborative structures in coastal sediment transport, emphasizing the pivotal role of numerical and empirical modeling. The findings not only map the knowledge structure but also suggest future research directions to strengthen predictive capabilities and inform sustainable coastal management practices.